William Sharpe correspondence and expense account - Sharpe, William, 1742-1818.
Expense account (1780 February 8) kept by Sharpe for his services as delegate to the U.S. Continental Congress from North Carolina and typewritten transcript of a letter (1781 April 7) from Sharpe to Gen. Nathanael Greene commenting on hardships faced by the Continental Army.
In part, typewritten transcript.
Delegate to U.S. Continental Congress from North Carolina, public official, lawyer, and surveyor.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Greene, Nathanael, -- 1742-1786 -- Correspondence; United States. -- Continental Army; United States. -- Continental Congress; Finance -- North Carolina; North Carolina -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783.; Delegates, U.S. Continental Congress -- North Carolina; Lawyers; Public officials -- North Carolina; Surveyors